Tamizado para identificar frijoles adaptados a suelos acidos - Thung, M.; Ortega, J.; Erazo, O (United Nations Development Programme, 1985)
General information on the nature of P, Al, and Mn and their interrelationship in the bean plant is presented. The methodology of screening to identify beans adapted to acid soils is indicated. This methodology includes site selection, determination of stress for Al, Mn, and P, simultaneous screening (on the basis of the former parameter), land preparation for planting and large-scale selection, modification of the screening methodology, and data collection and evaluation. Curves of response of some cv. to different P levels and to P as affected by N levels, yield curves, and lists of cv. efficient at low P and high Al and Mn levels are presented. (CIAT)